Segregação e Acondicionamento de Produtos Químicos: Implantação de um Sistema Seguro na Área de Química de Proteínas do Laboratório de Bioquímica e Biofísica – Instituto Butantan - Carlstron, Júlio Pacheco; Verreschi, Denise Ceravolo; Batista, Isabel de Fátima Correia; Tsubouchi, Beatriz de Moura; de Abreu, Bianca Cunha Guimarães; Mastantuno, Debora; Ito, Debora Tibana; Ramos, Pamella Wildmann; Szczygiel, Nara Luiza; Chudzinski-Tavassi, Ana Marisa; Cruz, Jose Arnaldo; Barazzone, Giovana Cappio; et al. (Orbital: The Electronic Journal of Chemistry, 2016)
Increasingly the production of chemical products has been made necessary and consequently there is a rise in the exposition to these materials and to its correlate effects, like operational risks, to the health and to the environment. In this way the segregation and storage programs of chemical products is extremely important. In face of this fact the Protein Chemistry Facility has established a safe handling and storage system for chemical products with the purchase/improvement of individual and collective protection equipment, making abridged safety records, structuring a proper area for keeping chemical products regarding compatibility and capacitation of related personnel. All these actions aim at the safety and well-being of all people on the area, plus minimization of environmental risks. DOI: http://dx.doi.org/10.17807/orbital.v8i3.874